Spectroscopic characterisation and thermodynamics of the complexation of Np(V) with sulfate up to 200 °C - Maiwald, Martin M.; Skerencak-Frech, Andrej; Panak, Petra (Spectrochimica acta. A, Molecular and biomolecular spectroscopy, 2020)
In the present work the complexation of Np(V) with sulfate in aqueous solution is studied in a temperature range up to 200 °C by absorption spectroscopy. For this purpose, a new spectroscopic setup is implemented and tested for its suitability for Vis/NIR absorption spectroscopy at elevated temperatures. The complexation of Np(V) with sulfate is studied as a function of the total ligand concentration at various temperatures (T = 25-200 °C) and ionic strengths (Im(NaClO4) = 1.0-4.0 mol kg−1 NaClO4). The exclusive formation of NpO2(SO4)− up to 200 °C is confirmed by peak deconvolution and slope analyses. The thermodynamic stability constants log β01(T) are obtained from linear regressions according to the specific ion interaction theory (SIT). A systematic increase of the log β01(T) is observed with increasing temperature, resulting in a linear correlation of log β01(T) with T−1. The magnitude of the increase is 1.9 logarithmic units at 200 °C in comparison to log β01(25 °C) = 1.05 ± 0.16. Thus, the standard reaction enthalpy and entropy (ΔrH0m, ΔrS0m) are determined with the integrated Van't Hoff equation revealing ΔrH0m = 31.0 ± 1.0 kJ mol−1 and ΔrS0m = 123 ± 9 J mol−1 K−1. In addition, the stoichiometric sum of the specific binary ion-ion interaction coefficient (Δε01(T)) is determined up to 200 °C showing an insignificant temperature dependence. Thus, a temperature-independent ε(Na+, NpO2(SO4)−) = 0.07 ± 0.11 is calculated for the temperature range up to 200 °C. Comparison of the present results with literature data confirms the excellent applicability of the new high-temperature absorption spectroscopic setup for complexation studies up to 200 °C.